TP8.1.9 Effect of Covid 19 on breast referrals from GP. (28th October 2021) - Sandhya, Anu; Narayan, Prabhat; Pogson, Caroline; Waheed, Shamaela; Singh, Jagdeep; Suleiman, Usama; Silva, Tania De
Abstract: Aim: Coronavirus disease 2019 (COVID-19) has put a strain on regular healthcare worldwide. This study shares a DGH experience of effect of covid 19 on breast referrals from GP. Methods: It is a single centre retrospective comparative study to analyze the effect of Covid 19 on breast referrals during the pandemic. Patients referred under TWR from 15 th march to 15 th July 2020 were included and a comparison was made with March to July 2019. The primary outcome was number of referrals and number of cancer diagnosis. Secondary outcomes were breach in 62 day pathway. Results: In Covid pandemic, 1231 symptomatic patient were referred under TWR, of which 91 (7.4%) were diagnosed with breast cancer. There were 22 (24%) 62 days breaches. Comparing this with similar 4 months in 2019 there were 1826 symptomatic patients referred under TWR of which 131 (7.1%) diagnosed with cancer. There were 34 screen detected cancers as well. There were 28 (21%)62 day breaches. The reduction in GP referral was 32%. Conclusion: There was an overall decrease in number of patients referred from GP but cancer diagnosis remained almost same for symptomatic patients since TWR pathway carried on with telephonic clinics & assessments at nearby closed screening centres.